Distributed event-triggered output consensus control for heterogeneous multi-agent system with general linear dynamics. Issue 11 (18th August 2017) - Liu, Xiangdong; Liu, Haikuo; Lu, Pingli; Guo, Shuli
ABSTRACT: This paper studies the distributed event-triggered output consensus problem of heterogeneous multi-agent system with general linear dynamics under an undirected connected graph. With the state-dependent triggering function, we design a novel distributed event-triggered output consensus controller for each agent to reach consensus with zero final consensus error. This strategy has several distinguishing features, including the fact that individual agent does not require continuous, or even periodic, communication with their neighbours to update the controller or monitor the triggering condition, and all parameters required by its implementation can be locally determined by the agent. We also prove that events cannot be triggered infinitely in finite time (i.e. no Zeno behaviour). Furthermore, the simulation examples are given to illustrate the theoretical analysis.